Effect of Interest Rates, Rupiah Exchange Rate, Fuel Prices, Household Consumption, and Government Expenditure on Inflation and Money Supply in Indonesia - Elfita, Nelfia; Ansofino, Ansofino; Jolianis, Jolianis (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the relationship between monetary and macroeconomic variables affecting inflation and the money supply in Indonesia from 1993 to 2024. Specifically, it examines the effects of the amount of money in circulation, interest rates, fuel prices, and government spending on inflation, as well as the effects of inflation, interest rates, exchange rates, and household consumption on the money supply. The research employs a quantitative approach using secondary data and applies a two-stage least squares (2SLS) simultaneous equation model with analysis conducted through the EViews program. The results indicate that the amount of money in circulation has a significant positive effect on inflation, while interest rates, fuel prices, and government spending show positive but insignificant effects. Conversely, inflation significantly influences the amount of money in circulation, while interest rates, the exchange rate, and household consumption have no significant effect. Simultaneously, both model equations demonstrate that the tested variables jointly have a significant impact on inflation and the money supply in Indonesia. These findings suggest that monetary expansion remains a key determinant of inflation dynamics in Indonesia, emphasizing the importance of prudent monetary policy and coordinated fiscal management.